1996
DOI: 10.1002/(sici)1096-9861(19961223)376:4<518::aid-cne2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal projections of cat extrastriate cortex: I. distribution and morphology of neurons projecting from posterior medial lateral suprasylvian sulcus to area 17

Abstract: Reciprocal projections between cortical areas have been subdivided into two functionally distinct component, "feedforward" and "feedback" (for review, see Felleman and Van Essen [1991] Cereb. Cortex 1:1-47). Some anatomical evidence, such as differences in the laminar distribution of the neurons of origin and of the terminations of their axons, has supported this division. However, very little is actually known about the distribution and morphology of the neurons of the feedback projections. In order to contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Electron microscopy has revealed that in rat cortex the AIS of axons originating from one of these major dendrites of inverted pyramidal cells are thinner ( Peters et al, 1968 ; Mendizabal-Zubiaga et al, 2007 ; Benavides-Piccione et al, 2020 ), and the initial segment is shorter and less innervated by symmetric synapses than AIS of axons arising from the soma ( Mendizabal-Zubiaga et al, 2007 ). In cat visual cortex, inverted-fusiform pyramidal neurons of layer VI serve corticocortical, but not corticothalamic projections; for instance, the feedback projection to area 17 from the suprasylvian sulcus ( Einstein, 1996 ), an area involved in motion detection, processing of optical flow, and pupillary constriction. With regard to the functional concept of AcD cells, the kinetics of intra- and interareal information processing may have so far unrecognized facets.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy has revealed that in rat cortex the AIS of axons originating from one of these major dendrites of inverted pyramidal cells are thinner ( Peters et al, 1968 ; Mendizabal-Zubiaga et al, 2007 ; Benavides-Piccione et al, 2020 ), and the initial segment is shorter and less innervated by symmetric synapses than AIS of axons arising from the soma ( Mendizabal-Zubiaga et al, 2007 ). In cat visual cortex, inverted-fusiform pyramidal neurons of layer VI serve corticocortical, but not corticothalamic projections; for instance, the feedback projection to area 17 from the suprasylvian sulcus ( Einstein, 1996 ), an area involved in motion detection, processing of optical flow, and pupillary constriction. With regard to the functional concept of AcD cells, the kinetics of intra- and interareal information processing may have so far unrecognized facets.…”
Section: Discussionmentioning
confidence: 99%
“…1992; Van Brederode & Snyder, 1992; Arimatsu et al. 1994; Einstein, 1 996; Matsubara et al. 1996; Zhong‐Wei & Deschenes, 1 997; Prieto & Winer, 1 999; Qi et al.…”
Section: Spiny Inverted Neuronsmentioning
confidence: 99%
“…In cats (Einstein & Fitzpatrick, 1 991; Einstein, 1 996) and macaque monkeys (De Lima et al. 1990), spiny inverted neurons are callosal and ipsilateral cortico‐cortical projection cells.…”
Section: Spiny Inverted Neuronsmentioning
confidence: 99%
“…Electron microscopy has revealed that the AIS of axons originating from the apical dendrite of rat inverted pyramidal cells are shorter, thinner and less innervated by symmetric synapses than AIS of axons arising from the soma . In cat visual cortex, inverted-fusiform pyramidal neurons of layer VI serve corticocortical, but not corticothalamic projections; for instance, the feedback projection to area 17 from the suprasylvian sulcus (Einstein, 1996), an area involved in motion detection, processes optical flow and pupillary constriction. With regard to the functional concept of AcD cells, the kinetics of intra-and interareal information processing may have so far unrecognized facets.…”
Section: Discussionmentioning
confidence: 99%